Peran Organisasi dalam Pencegahan Pelecehan Sesksual pada Anak (Studi Kasus Dinas Sosial Kabupaten Nias) - Roni Triswan Bate’e; Palindungan Lahagu; Odaligoziduhu Halawa; Syah Abadi Mendrofa (Jurnal Publikasi Manajemen Informatika, 2025)
Sexual harassment is an act involving exploitation and abuse of power of a sexual nature that degrades a person's dignity. This may include unwanted and inappropriate speech, behavior or physical actions that target someone based on their gender or sexual characteristics. The Nias District Social Service has a central role in providing social services to the community, including vulnerable groups who are more at risk of becoming victims of sexual harassment. This research aims to determine the roles and responsibilities, policies and effectiveness of Nias Regency as a region with cultural and social diversity that has its own challenges in maintaining an environment that is safe from sexual harassment. The Nias District Social Service has a central role in providing social services to the community, including vulnerable groups who are more at risk of becoming victims of sexual harassment. This research uses a qualitative research approach. The results of this research show that the Nias District Social Service has taken a number of concrete steps to prevent sexual abuse of children. These steps include regular education and training for organizational members, building an open and safe culture, and providing support for individuals in need. However, the effectiveness of these measures requires in-depth evaluation. Factors such as the level of response to policies, effectiveness of training, openness in organizational culture, availability of support, and ongoing evaluation processes need to be considered.